HUBUNGAN CARA BELAJAR DAN KELENGKAPAN SARANA BELAJAR DI RUMAH DENGAN PRESTASI BELAJAR GEOGRAFI SISWA - Aprilia Endra Dewi; Sumadi Sumadi; I Gede Sugiyanta (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to find out the relationship of students’ geography learning achievement between students’ learning method and completeness of learning tools at the second grade of social class of SMAN Tugumulyo Musi Rawas regency Sumatera Selatan in the year of 2012/2013. The method used was the correlational research method and the population was the second grade social students of SMA Negeri Tugumulyo, who were 160 students and  were taken 79 students as sample. The data collection techniques used in the research were questionnaire, interview, and documentation. The data were analyzed using Product Moment correlation, the results showed that: 1. There was a positive and significant relationship between students’ learning method and students’ geography learning achievement, and it was obtained the correlation coefficient (r) 0.806. 2. There was a positive and significant relationship between completeness of learning tools and students’ geography learning achievement, and it was obtained the correlation coefficient (r)0.750. 3. There was a positive and significant relationship between students’ learning method and completeness of learning tools, and it was obtained the correlation coefficient (r) 0.837. Keywords: Learning Method, Completeness of Learning Tools, Learning Achievement